Electronic Structure and Magnetic Properties of a Low-Spin CrIIComplex: Trans-[CrCl2(dmpe)2] (dmpe = 1,2-Bis(dimethylphosphino)ethane) - Zolnhofer, Eva; Opalade, Adedamola A.; Jackson, Timothy A.; Heinemann, Frank Wilhelm; Meyer, Karsten; Krzystek, J.; Ozarowski, Andrew; Telser, Joshua (Inorganic Chemistry, 2021)
Octahedral coordination complexes of the general formula trans-[MX2(R2ECH2CH2ER2)2] (MII = Ti, V, Cr, Mn; E = N, P; R = alkyl, aryl) are a cornerstone of both coordination and organometallic chemistry, and many of these complexes are known to have unique electronic structures that have been incompletely examined. The trans-[CrCl2(dmpe)2] complex (dmpe = Me2PCH2CH2PMe2), originally reported by Girolami and co-workers in 1985, is a rare example of a six-coordinate d4 system with an S = 1 (spin triplet) ground state, as opposed to the high-spin (S = 2, spin quintet) state. The ground-state properties of S = 1 systems are challenging to study using conventional spectroscopic methods, and consequently, the electronic structure of trans-[CrCl2(dmpe)2] has remained largely unexplored. In this present work, we have employed high-frequency and -field electron paramagnetic resonance (HFEPR) spectroscopy to characterize the ground-state electronic structure of trans-[CrCl2(dmpe)2]. This analysis yielded a complete set of spin Hamiltonian parameters for this S = 1 complex: D = +7.39(1) cm-1, E = +0.093(1) (E/D = 0.012), and g = [1.999(5), 2.00(1), 2.00(1)]. To develop a detailed electronic structure description for trans-[CrCl2(dmpe)2], we employed both classical ligand-field theory and quantum chemical theory (QCT) calculations, which considered all quintet, triplet, and singlet ligand-field states. While the high density of states suggests an unexpectedly complex electronic structure for this "simple"coordination complex, both the ligand-field and QCT methods were able to reproduce the experimental spin Hamiltonian parameters quite nicely. The QCT computations were also used as a basis for assigning the electronic absorption spectrum of trans-[CrCl2(dmpe)2] in toluene.
CRIS-Team Scopus Importer:2021-11-26